Program Saring Sebelum Sharing untuk Meningkatkan Kemampuan Verifikasi Hoaks Siswa SMP - Wayan Wirayana; Hans prismanta sembiring; Muhammad aldi nur haq; Zeskind Loveressaa; Supriyadin Supriyadin; Ilham Muhammad Ridho (CV. ITTC INDONESIA, 2026)
The rapid growth of digital media has increased adolescents' access to information while also exposing them to misinformation and hoaxes. Limited information verification skills highlight the need for practical digital literacy programs. This article describes the dissemination of the